Mother's Behavior and Knowledge in Preventing Stunting Through Breastfeeding Complementary Feeding to Children Aged 6-24 Months - Sudarianti; Rini Susanti; Ruri Aditya Sari (Institute of Computer Science (IOCS), 2022)
Parenting of babies and young children is the key to improving the survival of the child and encouraging growth. The method of collecting data by distributing questionnaires to 30 mothers who have babies of 6-24 months, the analysis carried out is mapping behavior and knowledge related to complementary foods and their correlation to stunting. Purposive sampling carries out the sampling technique. Based on the chi-square test, there was a relationship between respondents' knowledge and the condition of the baby with a smaller p value of 0.05, namely (p = 0.026). Based on the chi-square test, there was a relationship between respondents' attitudes and the condition of the baby with a p value smaller than 0.05, namely (p = 0.019). Based on the chi-square test, there was a relationship between the respondent's actions and the condition of the baby with a p value smaller than 0.05, namely (p = 0.004). Complementary foods for babies are already given to babies from a very early age (under the month), so the amount of nutrients that the baby needs is not in accordance with the needs of the child.